Kejahatan Kerah Putih, Kontraterorisme dan Perlindungan Hak Konstitusi Warga Negara dalam Bidang Ekonomi - Frassminggi Kamasa (The Constitutional Court of the Republic of Indonesia, 2016)
This article reviews the relationship between white-collar crimes, terrorism, and Indonesia’s counterterrorism policy. Indonesia’s counterterrorism policy yet include white-collar crimes, especially in economy, monetary, and banking, as a form of terrorism. This is because two things: the ignorance of the law enforcements on the white-collar crimes’ modus operandi and its reality that growing fast due to the development in science and technology. As a result, although white-collar crimes are so destructive and growing rapidly but Indonesia’s legal instruments to date did not have an integrated codification of law to eradicate it. Furthermore, Indonesia’s counterterrorism policy looks lopsided because it focused on street crimes or blue-collar crimes, the crimes committed by the lower class strata in such vulgar, unsophisticated, and violent natures. That is in contrast with the white- collar crimes which are so corrupt, destructive, and wicked because it conducted in a sophisticated, fraudulent, and systematic way. Thus, if the definition of terrorism only focuses in the type of street crimes then the corrupt practices, fraud, and deception in the white-collar crimes will be difficult to unfold and it seemed even strengthened, protected, and ultimately have a great potential in undermining the national stability.